Running Head: School-Community Partnership Mitigates Student Truancy: The Case of a Seaman’s Son in Ghana - Donkor, Anthony Kudjo (Advances in Social Sciences Research Journal, 2015)
The author revisited the school site where a case study on parental involvement on their children’s education was held five years ago. This move was in response to a participant’s request during the research interview five years ago. The participant requested that the research findings of the study should not be left on the shelf to collect dust. The author therefore made a follow-up study to find out the impact of the previous study, including recommendations of the study on the students, institution and community. Participants’ contributions in the previous study were reviewed by the author. These include perceptions of parents of children in the school where the study took place, perceptions of community leaders, perceptions of teachers and the perceptions of school administrators on education. The follow-up study discussed a success story centered round a student, who played truancy and later became a hero. The outcome of the study confirmed the benefits derived from teamwork by parents, teachers, school administrators, community members as well as community leaders in educating a child. In addition, it laid bare the defects on children whose parents were not involved in their education. This study will be of great importance to teachers, parents, educational leaders, community leaders and community members in children’s education.